Novel Setting (Time): Monism and Pluralism - Qasem Issa, Dr. Hisham (Al-Adab Journal, 2021)
The novel is distinguished from other spatial arts like drawing, sculpting, and architecture not only in the setting (narrative time), but also in its linguistic contents, which are more flexible and capable of forming, and flowing in motion. Even linguistic issues are more flexible than artistic materials that are essential in other arts, including color, stone, and others. Settings (narrative time) are characterized by the possibility of (pluralism) across different temporal structures in one narrative moment, and in multiple narrative perspectives, while other arts possess this plural characteristic only in surreal or post-modernist formative works. Pluralism is a key pillar in the formations of time, and in plural narrative perspectives.